2016
DOI: 10.1055/s-0035-1562736
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium-Catalyzed Reactions of 1-Alkynyl Phosphine Oxides and Sulfides with Et3Al

Abstract: The interaction of 1-alkynyl phosphine oxides, sulfides, and selenides with Me 3 Al and Et 3 Al under zirconocene catalysis was studied. It has been found that the pathway of the reaction of 1-alkynyl phosphine derivatives with Et 3 Al strongly depends on the nature of the substrate and the solvent. The ethylalumination takes place in the case of 1-alkynyl phosphine oxides in hexane solvent. The reaction of 1-hexynyl phosphine oxide with Et 3 Al failed when dichloromethane was used as a solvent. Zirconium-cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, all our attempts to carry out the reaction of 1-(sec-butylsulfinyl)oct-1-yne with the zirconocene-ethylene complex (prepared in situ from Cp 2 ZrCl 2 and 2 equiv of EtMgBr) were unsuccessful. 1-(sec-Butylsulfinyl)oct-1-yne was inert even on treatment with excess Cp 2 ZrEt 2 (3.75 7 We explained this difference by a higher content of cationic organometallic species…”
Section: Scheme 1 the Zirconium-catalyzed Reaction Of 1-alkynyl Sulfoxides With Et 3 Almentioning
confidence: 95%
See 1 more Smart Citation
“…However, all our attempts to carry out the reaction of 1-(sec-butylsulfinyl)oct-1-yne with the zirconocene-ethylene complex (prepared in situ from Cp 2 ZrCl 2 and 2 equiv of EtMgBr) were unsuccessful. 1-(sec-Butylsulfinyl)oct-1-yne was inert even on treatment with excess Cp 2 ZrEt 2 (3.75 7 We explained this difference by a higher content of cationic organometallic species…”
Section: Scheme 1 the Zirconium-catalyzed Reaction Of 1-alkynyl Sulfoxides With Et 3 Almentioning
confidence: 95%
“…Indeed, 1alkynylphosphine oxides react with Et 3 Al in the presence of the Cp 2 ZrCl 2 catalyst according to the ethylalumination pathway, whereas 1-alkynylphosphines and 1-alkynylphosphine sulfides are converted, under the same conditions, into cycloalumination products, together with some desulfurization products (in the case of phosphine sulfides). 7 We suggested that this difference is caused by the different nature of interaction of the zirconocene complex with unsaturated functionally substituted substrates containing two different types of nucleophilic centers. In this respect, it was of interest to clarify whether a similar difference is retained for organosulfur acetylene derivatives such as 1alkynyl sulfides and sulfoxides.…”
mentioning
confidence: 99%
“…35,36 As an alternative, recently we developed regio-and stereoselective methods for the preparation of О-, N-, and P-containing alkenes by Cp 2 ZrCl 2catalyzed cycloalumination of propargyl and homopropargyl alcohols, propargylamines, 37 and 1-alkynylphosphines. 38 The efficiency of carboalumination for the synthesis of P-and S-containing alkenes was demonstrated by Cp 2 ZrCl 2 -catalyzed ethylalumination of 1-alkynyl phosphorus oxides 39 and methylalumination of alkynyl sulfones, sulfoxides, and sulfides. 40 Thus, carboalumination of alkynes is an efficient method for the synthesis of various functionally substituted alkenes.…”
mentioning
confidence: 99%
“…1 Previously, we developed methods for the preparation of 1-alkenyl phosphines and phosphine oxides based on Zr-catalyzed carboalumination of 1-alkynyl phosphines and phosphine oxides. 2,3 It has been found that the pathway of the reaction of 1-alkynyl phosphine derivatives with organoaluminum compounds strongly depends on the nature of the substrate and the solvent. The ethylalumination takes place under the action of Et 3 Al in the case of 1-alkynyl phosphines and phosphine oxides in hexane as the solvent.…”
mentioning
confidence: 99%